A comparative study of bronchopulmonary slowly adapting receptors between rabbits and rats. Issue 6 (28th March 2022) - Liu, Ping; Zelko, Igor N.; Yu, Jerry
Abstract: Pulmonary mechanosensory receptors provide important inputs to the respiratory center for control of breathing. However, what is known about their structure–function relationship is still limited. In these studies, we explored this relationship comparing bronchopulmonary slowly adapting receptor (SAR) units in rabbits and rats. In morphological studies, sensory units in tracheobronchial smooth muscle labeled with anti‐Na + /K + ‐ATPase (α3 subunit) were found to be larger in the rabbit. Since larger structures may result from increased receptor size or more numerous receptors, further examination showed receptor size was the same in both species, but more receptors in a structure in rabbits than rats, accounting for their larger structure. In functional studies, SAR units were recorded electrically in anesthetized, open‐chest, and artificially ventilated animals and responses to lung inflation were compared at three different constant airway pressures (10, 20, and 30 cmH2 O). At each level of the inflation, SAR discharge frequencies were found to be higher in rabbits than rats. We conclude that a relatively larger number of receptors in a sensory unit may be responsible for higher SAR activities in rabbit SAR units. Abstract : Comparison of pulmonary mechanosensory structures and electrical activities between rabbits and rats. Mechanosensory units have more sensors and activity in rabbits than in rats. Electrical activity of the sensory unit is directly related to the number of sensors.